COOPERATIVE MODELS OF DOING BUSINESS AND THEIR ROLE IN FARMING COMMUNITY DEVELOPMENT - T. Atanassova-Kalaydzhievа (Trakia Journal of Sciences)
A collective business model with a specific character, distinguishing it from personal and capital companies is the cooperative. The cooperative model has been refined over the years and has become one of the widespread models for managing factors of production and providing services to its members in almost all economic sectors and countries around the world. A cooperative is a voluntary association of natural persons who, through mutual assistance and cooperation under equal responsibility and rights, transfer part of their functions to a common enterprise. Co-operation has proven to be a successful business model for building joint production facilities for processing the primary plant and animal products of farmers, thus creating additional income for them. Based on the broad scope of the subject, I limit the purpose of development to highlight the advantages of the cooperative model for doing business in association (unification) of farmers on the example of several European countries. A main conclusion of the study is that cooperatives play a crucial role in the prosperity and socio-economic development of the farming community they serve and the rural areas in which they are located.